2022
DOI: 10.1371/journal.pone.0264122
|View full text |Cite
|
Sign up to set email alerts
|

Treatment standards for direct oral anticoagulants in patients with acute ischemic stroke and non-valvular atrial fibrillation: A survey among German stroke units

Abstract: Background Acute ischemic stroke (AIS) in patients with non-valvular atrial fibrillation (AF) despite oral anticoagulation (OAC) is a complex and insufficiently investigated setting. Potential strategies range from maintaining the current OAC to changing the substance class. We have queried the specific treatment standards on German stroke units (SUs). Methods By means of a standardized online questionnaire via SurveyMonkey™ (San Mateo, CA, USA), all clinical heads of German SUs were asked about their treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These therapeutic options were highly variable across different regions. For instance, while most German stroke neurologists favored switching between DOACs, 8 in an Irish study, thrombotic events during DOAC usage commonly prompted switching to warfarin treatment. 9 Nonetheless, in an epidemiologic study, adjustment of oral anticoagulant therapy collectively did not reduce subsequent ischemic stroke risk.…”
mentioning
confidence: 99%
“…These therapeutic options were highly variable across different regions. For instance, while most German stroke neurologists favored switching between DOACs, 8 in an Irish study, thrombotic events during DOAC usage commonly prompted switching to warfarin treatment. 9 Nonetheless, in an epidemiologic study, adjustment of oral anticoagulant therapy collectively did not reduce subsequent ischemic stroke risk.…”
mentioning
confidence: 99%
“…Fastner et al 45 conducted a survey of German stroke units about strategies for prophylaxis after an acute ischemic stroke in a pa- tient with AF despite NOAC treatment. They showed that practitioners are more likely to switch from VKA to NOAC than vice versa and are very likely to switch between different NOACs depending on individual patient factors (e.g., coagulation tests).…”
Section: Medical Management To Prevent Cardioembolism In Noac Failurementioning
confidence: 99%